Etherification studies on chalcone derivative with series of bromoalkanes - Nurazrina, Mohd Damanhuri (Universiti Malaysia Sarawak (UNIMAS), 2008)
This research consists of two strategies which consist of the synthesis of chalcone and the introduction of the alk yl groups. A series of I-bromoalkyl namely C6, C7, C8 and C9 were introduced to the hydroxychalcone which was prepared using Claisen-Schmidt condensation reaction between 4hydroxyacetophenone and benzaldehyde. Another strategy was carried out by alkylation of 4hydroxyacetophenone prior to the synthesis of chalcone derivatives. The infrared (FT-IR) and the nuclear magnetic resonance eH and I3C) spectroscopy were used to analyzed the compound. This study is perfOim ed to determine the best strategy that will produce higher yield. The study also involve measuring the antibacterial properties ofthe synthesized chalcone on biological assay.